Episodic memory decline symptoms are strong predictors of Alzheimers disease defined by Positron Emission Tomography in participants with amnestic mild cognitive impairment and mild dementia - Kittithatch Booncharoen; Akarin Hiransuthikul; Poosanu Thanapornsangsuth; Sekh Thanprasertsuk; Yuthachai Sarutikriangkri; Suchart Tangnimitchoke; Wanakorn Rattanawong; Kammant Phanthumchinda; Yuttachai Likitjaroen (My University, 2023)
Abstract Background The diagnosis of Alzheimer’s disease (AD) has been shifted from clinical to biomarker‐based approach. However, the disease‐specific biomarker investigations are either invasive, expensive, or unavailable. Episodic memory decline symptoms (EMDS) have been recognized as an early manifestation of AD. We aimed to determine the performance of integrating EMDS in predicting AD among participants with amnestic mild cognitive impairment (MCI) or mild dementia. Method Amnestic MCI and mild dementia participants were recruited from memory clinic at King Chulalongkorn Memorial Hospital, Thailand. In‐house informant‐based questionnaire was used to interview participants’ caregivers, which comprise of (A) 7 questions on changes in EMDS during the past 10 years and (B) 6 questions on the average daily frequency of EMDS in the previous month. Amyloid (Florbetaben) and Tau (PI‐2620) Positron Emission Tomography (PET) were performed. The result with A+T+ was defined as AD, the result with A+T‐ or A‐T‐ were define as other cognitive impairments. Multivariable logistic regression models were employed to construct the predictive model. The likelihood ratio test and area under the curve of receiver operating characteristic curve (AUC‐ROC) were used to identify the best model. Result Among 50 participants enrolled (median [interquartile range] age 72 [65‐77] years), 24 (48%) had AD. A comparison of AD and other cognitive impairments is shown in Table 1 . The combination of 3 symptoms, including (1) consistently worse in remembering events during the past 10 years; (2) at least once daily momentary confabulation; and (3) at least once daily repetitive questioning, had the best diagnostic performance in parsimonious model for predicting AD with AUC‐ROC of 0.77 (95% confidence interval [CI]: 0.64‐0.90). (Figure 1) Conclusion EMDS are still a valuable clinical marker for predicting AD in participants with amnestic MCI and mild dementia. The combination of selected EMDS might be a useful screening tool for selecting patients for further AD specific biomarker investigations.
Keywords: Interquartile range; Memory clinic; Cognitive Decline; Dementia and Cognitive Impairment Research